2007
DOI: 10.1016/j.dsr.2006.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Ocean control of the breeding regime of the sooty tern in the southwest Indian Ocean

Abstract: Abstract:Food availability, which is often seasonal, is regarded as a key factor in the breeding success of seabirds. In oceanic tropical areas, the resources are mostly patchy and ephemeral at the surface, and the seasonality is less marked than at higher latitudes. Such a situation influences greatly the breeding strategies of the oceanic seabird species. We conducted a comparative study of the breeding phenology of the sooty tern (Sterna fuscata) in relation to the local and regional oceanographic condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
37
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 54 publications
3
37
0
1
Order By: Relevance
“…We can therefore assume that breeding is not always synchronous between different islets and species at SBR, a condition that may be advantageous, but should be protected and managed as such (see Rocamora et al 2003, Feare et al 2007, Jaquemet et al 2007, Jaquemet et al 2008, and Catry et al 2009 for more on the breeding phenology of seabirds in the western Indian Ocean). Visits to some of the islets by tourists or for other reasons could be restricted to certain periods of the year, but this would require regular monitoring.…”
Section: Timing Of Bird Breeding Throughout Sbrmentioning
confidence: 99%
“…We can therefore assume that breeding is not always synchronous between different islets and species at SBR, a condition that may be advantageous, but should be protected and managed as such (see Rocamora et al 2003, Feare et al 2007, Jaquemet et al 2007, Jaquemet et al 2008, and Catry et al 2009 for more on the breeding phenology of seabirds in the western Indian Ocean). Visits to some of the islets by tourists or for other reasons could be restricted to certain periods of the year, but this would require regular monitoring.…”
Section: Timing Of Bird Breeding Throughout Sbrmentioning
confidence: 99%
“…We also made use of two climatic indices: Multi-variate ENSO Index (MEI) and Dipole Mode Index (DMI). Further details on the provenance, derivation and interpretation of all our data can be found in refs [2,5]. …”
Section: Environmental Datamentioning
confidence: 99%
“…By recording wing span and using recognised growth rates for terns [6], and subtracting a typical incubation period of 28 days, we deduce the likely laying dates. Typically all the birds in a colony lay within a short period; the typical standard deviation of observations being ~8 days (see [5] for full details). In the case of Bird Island, we make use of historical records of observations by Feare [6,7] The particularly interesting aspect of these results (Fig.…”
Section: Annual Cyclesmentioning
confidence: 99%
“…In Seychelles, egg laying by Sooty Terns Onychoprion fuscatus is highly synchronous (Feare 1976a, Jacquemet et al 2007, as evidenced by 75% of the estimated 395,000 eggs on Bird Island being laid within a nineday period in the 1973 breeding season (Feare 1976a), the only year that the pattern of laying has been closely followed. A corollary of synchrony is that pairs that laid during peak egg-laying reared more chicks to fledging than those that laid early or late in the season (Feare 1976a).…”
mentioning
confidence: 99%
“…A corollary of synchrony is that pairs that laid during peak egg-laying reared more chicks to fledging than those that laid early or late in the season (Feare 1976a). Three factors could account for this: social behaviour within the colony, involving aggression of adults and larger young to smaller chicks that enter their territories (Feare 1976a), a social component in the location of feeding opportunities that are unpredictable in space and time (Ashmole 1963), and a seasonal effect of food availability, which Jacquemet et al (2007) demonstrated from remote sensing of sea-surface temperatures and chlorophyll concentrations in surface waters around Seychelles.…”
mentioning
confidence: 99%